Synthesis, Spectral and Antimicrobial Studies of Lanthanide (III) Chloride Complexes with the Schiff’s Base Derived from 2-Benzimidazolyl Mercaptoaceto Hydrazide and 2-Acetyl Pyridine - N.B. Mallur*, S.K. Patil, V.M. Naik, D.C. Bilehal, and (Recent Research in Science and Technology, 2010)
Abstract Few lanthanide (III) chloride complexes with Schiff’s base obtained by the condensation of 2-benzimidazolyl mercaptoaceto hydrazide and 2-acetyl pyridine have been prepared and characterized on the basis of elemental analysis, molar conductance, magnetic, electronic, infrared and 1H NMR spectral studies, IR and 1H NMR spectra indicates coordination through azomethine nitrogen, pyridine ring nitrogen and the carbonyl oxygen of the hydrazone moiety. A coordination number eight is suggested for these complexes. The ligand and complexes were screened for their antimicrobial activity. Keywords: Schiffs base; Lanthanide (III) chloride complexes; Antimicrobial activity